Costing System in Sales Price (CSSP): analysis of results in small and medium-sized industrial companies located in RS (Brazil) - Schneider, José Inácio; Maldaner, Luís Felipe (Revista Liberato, 2021)
The overall objective of this study was to analyze the results of the implementation of the Costing System in Sales Price (CSSP), using a cost matrix that considers the distribution of indirect costs and fixed expenses in seven small and medium-sized industrial companies, located in “Serra Gaúcha” (RS), through a Reference Apportionment (RA) that parameterizes the revenue with the market value of each product. Data were collected in the year 2015. This study also contextualizes and provides a cost structure in a format similar to the Income Statement (IS), using, as main information source, the accounting data, financial records, analysis of accounting books and production data which were combined with semi-structured interviews. To sum up, this research has established the Costing System in Sales Price (CSSP) and the Reference Apportionment (RA) as criteria for distribution of indirect costs, reinforcing the idea that the sales price should follow the market logic.